The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3892/ijmm.2017.3112
|View full text |Cite
|
Sign up to set email alerts
|

EWS-FLI1 positively regulates autophagy by increasing ATG4B expression in Ewing sarcoma cells

Abstract: Ewing sarcoma (ES) is the most common malignant bone tumor in children and young adults. It is characterized by chromosomal translocations fusing the EWS gene with an ETS oncogene, most frequently FLI1. In the present study, the authors aimed to investigate the function of EWS-FLI1 in autophagy in ES cells, and identified that EWS-FLI1 positively regulates autophagy in ES cells. ATG4B expression was observed markedly upregulated by EWS-FLI1 overexpression, and silencing of ATG4B dramatically inhibits autophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Autophagy plays great roles in the clearance of longlived proteins, aggregates and damaged organelles, and dysregulation of autophagy is highly associated with cancer, particularly in tumorigenesis and chemotherapy resistance. 13 In the current study, we found that TRIM3 could regulate autophagy in ES cells. Overexpression of TRIM3 significantly inhibits autophagy, as evidenced by the increases in the amount of P62 (SQSTM1) and decreases in the amount of LC3B-II, two important markers of autophagy, as well as the increased LC3 puncta in cells.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Autophagy plays great roles in the clearance of longlived proteins, aggregates and damaged organelles, and dysregulation of autophagy is highly associated with cancer, particularly in tumorigenesis and chemotherapy resistance. 13 In the current study, we found that TRIM3 could regulate autophagy in ES cells. Overexpression of TRIM3 significantly inhibits autophagy, as evidenced by the increases in the amount of P62 (SQSTM1) and decreases in the amount of LC3B-II, two important markers of autophagy, as well as the increased LC3 puncta in cells.…”
Section: Discussionmentioning
confidence: 50%
“…In previous study, we found that EWS-FLI1 promotes autophagy in ES cells, 13 therefore we supposed if TRIM3 could also regulate autophagy. Overexpression of TRIM3 in TC71 cells was confirmed as shown in Figure 3A.…”
Section: Overexpression Of Trim3 Inhibited Autophagy In Es Cellsmentioning
confidence: 89%
“…The translocation fusion between EWS and ETS family members produces a potent oncogenic transcription factor 177 capable of inducing tumorigenesis through increased cell viability and proliferation, 178 181 apoptosis inhibition, 180 metabolic changes to favor biosynthesis, and subsequent cell division. 182 EWS – ETS regulates cell proliferation and anchorage-independent growth in ES cells, but not in a non-ES cell line.…”
Section: Ewing’s Sarcomamentioning
confidence: 99%
“… 181 Additionally, EWS – ETS induces autophagy in ES through overexpression of an autophagy-related gene, ATG4B , which leads to a higher rate of proliferation and lower rate of apoptosis. 180 Metabolism in ES is also altered due to EWS – ETS oncogenic regulation, which increases serine biosynthesis via PGHDH upregulation, for the production of proteins, lipids, and nucleic acids to meet the demands of cell proliferation. 182 Interestingly, elevated PGHDH expression is highest in ES compared to other cancer cell lines, as well as normal tissue, and patients who are deemed at high risk show upregulation in PGHDH.…”
Section: Ewing’s Sarcomamentioning
confidence: 99%
“…In the past studies of ES, it has been reported that autophagy-related genes are closely related to the development of ES. For example, TRIM3 negatively regulates autophagy by promoting the degradation of Beclin1 in ES cells, eWS-FLI1 actively regulates autophagy by increasing the expression of ATG4B in ES cells [11]. However, the relationship between autophagy-related genes and the prognosis of ES patients is still unknown.…”
Section: Introductionmentioning
confidence: 99%